The EEG effects of THIP (Gaboxadol) on sleep and waking are mediated by the GABA(A)delta-subunit-containing receptors. - Winsky-Sommerer, R; Vyazovskiy, V; Homanics, G; Tobler, I (2007)
THIP (4,5,6,7-tetrahydroisoxazolo-[5,4-c]pyridine-3-ol, Gaboxadol) is a selective gamma-aminobutyric acid (GABA)(A) agonist, acting in vitro with high potency and efficacy at the extrasynaptic GABA(A)delta-containing receptors. THIP was suggested to be a potential hypnotic to treat insomnia, and it is currently in clinical trial. Here we assessed whether the GABA(A)delta-containing receptors mediate in vivo the effect of THIP on sleep and the sleep electroencephalogram (EEG). We performed EEG recordings in a mouse model deficient in the GABA(A)delta-subunit gene (delta(-/-) mice) and in wild-type littermate controls. THIP (4 and 6 mg/kg intraperitoneally) induced an abnormal EEG pattern, resulting in dramatic changes in the waking and non-rapid eye movement (NREM) sleep EEG spectra in wild-type mice. Indeed, a massive increase in EEG power lasting 2-3 h occurred in both the frontal and parietal derivation, especially in frequencies below 6 Hz. All effects were more prominent in the frontal EEG. Furthermore, the highest dose of THIP lengthened REM sleep latency and suppressed REM sleep. In contrast, vigilance states and sleep latencies were not affected in delta(-/-) mice. Moreover, only minor changes were observed in the NREM sleep EEG spectrum after THIP injection in the delta-subunit-deficient mice. The present findings do not indicate a sleep-promoting effect of THIP in mice, which is in accordance with a previous report in this species. Moreover, our results in vivo demonstrate that THIP acts preferentially at GABA(A) receptors containing the delta-subunit.